Alteration of brain dynamics during dual‐task overground walking. (15th September 2020) - Nenna, Federica; Do, Cao Tri; Protzak, Janna; Gramann, Klaus
Abstract: When walking in our natural environment, we often solve additional cognitive tasks. This increases the demand of resources needed for both the cognitive and motor systems, resulting in Cognitive‐Motor Interference (CMI). A large portion of neurophysiological investigations on CMI took place in static settings, emphasizing the experimental rigor but overshadowing the ecological validity. As a more ecologically valid alternative to treadmill and desktop‐based setups to investigate CMI, we developed a dual‐task walking scenario in virtual reality (VR) combined with Mobile Brain/Body Imaging (MoBI). We aimed at investigating how brain dynamics are modulated by dual‐task overground walking with an additional task in the visual domain. Participants performed a visual discrimination task in VR while standing (single‐task) and walking overground (dual‐task). Even though walking had no impact on the performance in the visual discrimination task, a P3 amplitude reduction along with changes in power spectral densities (PSDs) were observed for discriminating visual stimuli during dual‐task walking. These results reflect an impact of walking on the parallel processing of visual stimuli even when the cognitive task is particularly easy. This standardized and easy to modify VR paradigm helps to systematically study CMI, allowing researchers to control for the impact of additional task complexity of tasks in different sensory modalities. Future investigations implementing an improved virtual design with more challenging cognitive and motor tasks will have to investigate the roles of both cognition and motion, allowing for a better understanding of the functional architecture of attention reallocation between cognitive and motor systems during active behavior. Abstract : The neural foundations of Cognitive‐Motor Interference (CMI) were investigated within an ecologically valid dual‐task walking paradigm in the visual domain, by combining virtual reality (VR) with Mobile Brain/Body Imaging (MoBI). A P3 amplitude reduction along with changes in power spectral densities (PSDs) were observed for discriminating visual stimuli during dual‐task walking. This VR paradigm helps to systematically study CMI, allowing to manipulate task complexity and sensory modalities.